2021
DOI: 10.3171/2020.1.jns192914
|View full text |Cite
|
Sign up to set email alerts
|

Spreading depolarization may represent a novel mechanism for delayed fluctuating neurological deficit after chronic subdural hematoma evacuation

Abstract: OBJECTIVEMost patients with chronic subdural hematoma (cSDH) recover after surgical evacuation with a straightforward course. There is a subset of patients who develop transient and fluctuating deficits not explained by seizures, stroke, or mass effect after evacuation. The objective of this study was to investigate whether these postoperative neurological deficits may be related to temporary brain dysfunction caused by cortical spreading depolarizations (SDs). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Accordingly, SD is observed as a large negative direct current (DC) shift, two-photon microscopy shows neuronal swelling with a beaded morphology of neuronal dendrites during SD [2], and magnetic resonance imaging shows a propagating wave of diffusion restriction [3][4][5]. SDs occur during a plethora of clinical conditions, including migraine aura [6,7], ischemic stroke [8,9], traumatic brain injury [10,11], aneurysmal subarachnoid hemorrhage (aSAH) and delayed ischemic stroke [12][13][14], spontaneous intracerebral hemorrhage [15], subdural hematoma [16], development of brain death [17,18], and dying from circulatory arrest [19]. The SD continuum describes the spectrum from transient events of intermediate duration to short duration in less ischemic or adequately supplied tissue to terminal SDs in severely ischemic tissue characterized by the transition of the neurons from the state of injury to cell death [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SD is observed as a large negative direct current (DC) shift, two-photon microscopy shows neuronal swelling with a beaded morphology of neuronal dendrites during SD [2], and magnetic resonance imaging shows a propagating wave of diffusion restriction [3][4][5]. SDs occur during a plethora of clinical conditions, including migraine aura [6,7], ischemic stroke [8,9], traumatic brain injury [10,11], aneurysmal subarachnoid hemorrhage (aSAH) and delayed ischemic stroke [12][13][14], spontaneous intracerebral hemorrhage [15], subdural hematoma [16], development of brain death [17,18], and dying from circulatory arrest [19]. The SD continuum describes the spectrum from transient events of intermediate duration to short duration in less ischemic or adequately supplied tissue to terminal SDs in severely ischemic tissue characterized by the transition of the neurons from the state of injury to cell death [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of CSD in patients with SDH proved to be a marker for worse prognostic outcome, 39 while the presence of NESIS, believed to be a marker of CSD, was associated with favorable outcome in two distinct studies. 7,10 Although the different study design limits the possibility for direct comparisons, such discrepancies could be related to the different population studied.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using ECoG in 40 patients with chronic SDH post-surgical evacuation revealed the presence of definite CSD in 15% of patients post-surgical evacuation (independent of the presence or absence of TNS). 39 One of the cases demonstrated a time-lock focal neurological deterioration at the onset of CSD clusters with no alternative causal explanation on MRI or EEG supporting that his TNS may have been directly caused by the CSD. The presence of CSD proved to be of prognostic significance and was associated with postoperative neurological deterioration in 50% compared to 8.8% in the subgroup without evidence of CSD.…”
Section: Cortical Depolarization In Subdural Hemorrhage: Connecting Tmentioning
confidence: 93%
“…SDs are pathologic waves in cerebral gray matter defined by the near-complete breakdown of electrochemical membrane gradients, with consequent silencing of electrical activity (spreading depression) [5]. The hypothesis that SDs underlie some of these syndromes is supported by the known role of SDs in delayed neurological injury [5], including in patients with cSDH [6].In this issue of Neurocritical Care, Meadows et al[7] expand on prior work by examining the clinical characteristics and significance of definite and "probable" SDs in postoperative patients with cSDH. The authors combined two cohorts for this study: one cohort consisted of prospectively enrolled patients with cSDH with strip electrodes, whereas a second and larger cohort consisted of postoperative patients with cSDH who underwent usual care without a strip electrode.…”
mentioning
confidence: 99%
“…SDs are pathologic waves in cerebral gray matter defined by the near-complete breakdown of electrochemical membrane gradients, with consequent silencing of electrical activity (spreading depression) [5]. The hypothesis that SDs underlie some of these syndromes is supported by the known role of SDs in delayed neurological injury [5], including in patients with cSDH [6].…”
mentioning
confidence: 99%